2020
DOI: 10.3389/fpls.2020.00491
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of Cells From Bell Pepper (Capsicum annuum) Infected With Bell Pepper Endornavirus

Abstract: Endornaviruses include viruses that infect fungi, oomycetes, and plants. The genome of plant endornaviruses consists of linear ssRNA ranging in size from approximately 13-18 kb and lacking capsid protein and cell-to-cell movement capability. Although, plant endornaviruses have not been shown to cause detectable changes in the plant phenotype, they have been associated with alterations of the host physiology. Except for the association of cytoplasmic vesicles with infections by Vicia faba endornavirus, effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…These genes have been reported to be involved in the plant defense response. This is not surprising as it has been reported that BPEV can cause cellular ultrastructural changes in bell pepper ( Otulak-Koziel et al, 2020 ). Transcriptomic analysis of two lines (not NILs) of common bean, one infected with Phaseolus vulgaris endornavirus and the other endornavirus-free, revealed several upregulated genes involved in response to pathogen infection and environmental stresses ( Khankhum et al, 2016 ).…”
Section: Resultssupporting
confidence: 55%
“…These genes have been reported to be involved in the plant defense response. This is not surprising as it has been reported that BPEV can cause cellular ultrastructural changes in bell pepper ( Otulak-Koziel et al, 2020 ). Transcriptomic analysis of two lines (not NILs) of common bean, one infected with Phaseolus vulgaris endornavirus and the other endornavirus-free, revealed several upregulated genes involved in response to pathogen infection and environmental stresses ( Khankhum et al, 2016 ).…”
Section: Resultssupporting
confidence: 55%
“…Further, Yang et al found that Sclerotinia minor endornavirus 1 (SmEV1) has horizontal and vertical transmission characteristics, and the mycelium fragments of strain LC22 can attenuate the virulence of S. minor [ 37 ]. Recent studies have found that plants infected by Bell pepper endornavirus (BPEV) have alterations of organelles and other cell components, which are believed to be caused by parasitic effects between the endornavirus and host [ 53 ]. Additionally, the coinfection of Phytophthora endornavirus 2 (PEV2) and Phytophthora endornavirus 3 (PEV3) also affects the sensitivity of oomycetes to fungicides [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genomes contain one open reading frame (ORF), which encodes a single polyprotein consisting of 3,217–5,825 amino acid (aa) residues with several conserved domains, such as RNA-dependent RNA polymerase (RdRP), helicase (Hel), and UDP-glucosyl transferase (UGT) ( Valverde et al, 2019 ). Although endornaviruses have not been reported to possess capsid proteins, they have been suggested to be associated with vesicular membranes in the cytoplasm ( Lefebvre et al, 1990 ; Moriyama et al, 1996 ; Horiuchi et al, 2003 ; Otulak-Kozieł et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%